2013
DOI: 10.1177/0300985813505117
|View full text |Cite
|
Sign up to set email alerts
|

Safety Biomarkers in Preclinical Development

Abstract: The identification, application, and qualification of safety biomarkers are becoming increasingly critical to successful drug discovery and development as companies are striving to develop drugs for difficult targets and for novel disease indications in a risk-adverse environment. Translational safety biomarkers that are minimally invasive and monitor drug-induced toxicity during human clinical trials are urgently needed to assess whether toxicities observed in preclinical toxicology studies are relevant to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…The goal for new predictive translational safety biomarkers is to be able to monitor early indications of organ toxicity in clinical trials, so better informed clinical and regulatory decisions can be made and treatment can be stopped or altered before organ injury occurs (Aronson 2005 ; Matheis et al 2011 ; Sistare and DeGeorge 2011 ). The ideal characteristics of translational safety biomarkers of organ injury are that they provide more sensitive and specific information than current clinical chemistry biomarkers, can be detected through robust analytical assays in relevant translational species (rat, dog, mouse or monkey) and in humans, can be measured noninvasively or in accessible fluids like blood or urine, can predict or monitor severity of histopathology in nonclinical species, are specific for organ injury or mechanisms of toxicity that lead to organ injury, are specific to tissue location and are insensitive to nontoxic perturbations (exercise, diet, age, and other diseases and toxicities to other organs) (Amacher 2010 ; Muller and Dieterle 2009 ; Sasseville et al 2014 ; Sistare and DeGeorge 2011 ; Mattes personal communication). The translational aspect, i.e., the ability of the biomarker to have similar responses in different species, enables comparisons of nonclinical studies with clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The goal for new predictive translational safety biomarkers is to be able to monitor early indications of organ toxicity in clinical trials, so better informed clinical and regulatory decisions can be made and treatment can be stopped or altered before organ injury occurs (Aronson 2005 ; Matheis et al 2011 ; Sistare and DeGeorge 2011 ). The ideal characteristics of translational safety biomarkers of organ injury are that they provide more sensitive and specific information than current clinical chemistry biomarkers, can be detected through robust analytical assays in relevant translational species (rat, dog, mouse or monkey) and in humans, can be measured noninvasively or in accessible fluids like blood or urine, can predict or monitor severity of histopathology in nonclinical species, are specific for organ injury or mechanisms of toxicity that lead to organ injury, are specific to tissue location and are insensitive to nontoxic perturbations (exercise, diet, age, and other diseases and toxicities to other organs) (Amacher 2010 ; Muller and Dieterle 2009 ; Sasseville et al 2014 ; Sistare and DeGeorge 2011 ; Mattes personal communication). The translational aspect, i.e., the ability of the biomarker to have similar responses in different species, enables comparisons of nonclinical studies with clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The same model has been used to address developmental disruption caused by bisphenol A, with results in concordance with those reported in a mouse model (Mathisen et al, 2013). Histopathology remains the gold standard (Sasseville et al, 2014) for assessing detrimental effects on the developing CNS in chickens (Table 1). In addition, there are several biomarkers that could be useful for early screening purposes, although few are firmly established.…”
Section: Expanding the Use Of The Chicken Embryo Modelmentioning
confidence: 54%
“…6 The gap is narrowed by identification and application of biomarkers critical for successful drug discovery and development. 7 Translational safety biomarkers that are minimally invasive and monitor drug-induced toxicity during human clinical trials are essential for assessing toxicities observed in preclinical toxicology studies necessary to determine therapeutic doses. The data obtained during the biomarker qualification phase includes careful consideration of the analytic method used, the biology, pharmacokinetic and pharmacodynamic properties of the biomarker, and the pathophysiology of the process studied.…”
Section: Editorialmentioning
confidence: 99%